Sidestream dark field imaging of the serosal microcirculation during gastrointestinal surgery. (March 2016) - de Bruin, A. F. J.; Kornmann, V. N. N.; van der Sloot, K.; van Vugt, J. L.; Gosselink, M. P.; Smits, A.; Van Ramshorst, B.; Boerma, E. C.; Noordzij, P. G.; Boerma, D.; van Iterson, M.
Abstract: Aim: The study aimed to describe the serosal microcirculation of the human bowel using sidestream dark field imaging, a microscopic technique using polarized light to visualize erythrocytes through capillaries. We also compared its feasibility to the current practice of sublingual microcirculatory assessment. Method: In 17 patients sidestream dark field measurements were performed during gastrointestinal surgery. Microcirculatory parameters like microvascular flow index (MFI), proportion of perfused vessels (PPV), perfused vessel density (PVD) and total vessel density (TVD) were determined for every patient, sublingually and on the bowel serosa. Results: Sixty measurements were done on the bowel of which eight (13%) were excluded, five owing to too much bowel peristalsis and three because of pressure artefacts. Image stability was in favour of sublingual measurements [pixel loss per image, bowel 145 (95% CI 126–164) vs sublingual 55 (95% CI 41–68); P < 0.001] and time to acquire a stable image [bowel 96 s (95% CI 63–129) vs sublingual 46 s (95% CI 29–64); P = 0.013]. No difference in the MFI was observed [bowel 2.9 (interquartile range 2.87–2.95) vs sublingual 3.0 (interquartile range 2.91–3.0); P = 0.081]. There was a difference in the PPV [bowel 95% (95% CI 94–96) vs sublingual 97% (95% CI 97–99); P < 0.001], PVD [bowel 12.9 mm/mm 2 (95% CI 11.1–14.8) vs sublingual 17.4 mm/mm 2 (95% CI 15.6–19.1); P = 0.003] and the TVD [bowel 13.6 mm/mm 2 (95% CI 11.6–15.6) vs sublingual 17.7 mm/mm 2 (95% CI 16.0–19.4); P = 0.008]. Conclusion: Sidestream dark field imaging is a very promising technique for bowel microcirculatory visualization and assessment. It is comparable to sublingual assessment and the analysis produces a similar outcome with slightly differing anatomical features.